Influence of cation substitution on cycling stability and Fe-cation migration in Li3Fe3–xMxTe2O12 (m = Al, In) cathode materials - Martínez de Irujo Labalde, X; Lee, MY; Grievson, H; Mortimer, J-M; Booth, SG; Suard, E; Cussen, SA; Hayward, MA (American Chemical Society, 2024)
Li3Fe3Te2O12 adopts a crystal structure, described in space group Pnnm, related to that of LiSbO3, in which Te6+, Fe3+, and Li+ cations reside in a partially ordered configuration within an hcp array of oxide ions. Chemical or electrochemical insertion of lithium is accompanied by a fully reversible migration of some of the Fe cations with an initial capacity of 120 mA h g–1 (2.85 Li per formula unit). Long-term cycling stability is limited by the facile reduction of Te6+ to elemental Te, which leads to cathode decomposition. Partial substitution of Fe by In suppresses Te6+ reduction, such that Li3Fe2InTe2O12 shows no sign of this cathode decomposition pathway, even after 100 cycles. In contrast, Al-for-Fe substitution is chemically limited to Li3Fe2.6Al0.4Te2O12 and appears to have almost no influence on cathode longevity. These features of the Li3Fe3-xMxTe2O12 system are discussed on the basis of a detailed structural analysis performed using neutron and synchrotron X-ray diffraction.